Annual Plan 1990-91 Plan-Budget Link - Planning Commission (Planning Commission, 1990)
This volume aims at presenting the Annual Plan Outlay for 1990-91 as emerging from the budget Estimate for 1990-91. the Annual Plan for 1990-91 marks the beginning and is the first year of the Eight Five-Year Plan. The Annual Plan has been prepared generally on the objectives proposed to be set out in the Eighth Plan.
Plan-Budget Link
Finance Department